1995
DOI: 10.3109/00016489509133351
|View full text |Cite
|
Sign up to set email alerts
|

Polyp Pathogenesis-A Histopathological Study in Experimental Otitis Media

Abstract: We examined the mucosa of 50 rat middle ears in an experimental model of acute otitis media, in order to obtain information on the mechanisms of polyp formation. The right middle ear of 25 rats was inoculated with type 3 pneumococci, and the left ear served as a control. The animals were killed, the middle ear bulla removed, and the mucosa was dissected from the bone, stained PAS-alcian blue and embedded as a whole-mount. The whole-mounts were examined in a light microscope for polypous mucosal prominences. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
2
21
0
2
Order By: Relevance
“…Another interesting phenomenon is that H. in uenzae tended to cause rupture of the basement membrane, adhesion of the middle ear mucosa and formation of localized compartments in the middle ear cavity. In agreement with this, studies done by Caye-Thomasen and Tos (9) and by Larsen and Tos (10) demonstrated that both H. in uenzae type b and NTHi caused polyp and brous adhesion formation in the middle ear of rats, whereas S. pneumoniae did not (11).…”
Section: Discussionsupporting
confidence: 63%
“…Another interesting phenomenon is that H. in uenzae tended to cause rupture of the basement membrane, adhesion of the middle ear mucosa and formation of localized compartments in the middle ear cavity. In agreement with this, studies done by Caye-Thomasen and Tos (9) and by Larsen and Tos (10) demonstrated that both H. in uenzae type b and NTHi caused polyp and brous adhesion formation in the middle ear of rats, whereas S. pneumoniae did not (11).…”
Section: Discussionsupporting
confidence: 63%
“…12 The excessive repair processes after repeated airway injury would lead to the remodeled phenotype found in NPs. Wound healing is characterized by the appearance of many ECM components in a spatial and sequential pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation and changes in morphological structure of these secretions might be influenced by various factors postulated in nasal polyp etiopathogenesis. These clinical and histologic observations seem more plausible in explaining nasal polyp pathogenesis than do those of larsen et al, 18 Cayé-Thomasen et al, 19 and Hsu et al, 20 who suggest that prolapse of the fibrous tissue of the lamina propria through an epithelial defect is followed by re-epithelialization of the protruded tissue to form a polyp.…”
Section: Resultsmentioning
confidence: 79%